Longitudinal Rehabilitation of Binocular Function in Adolescent Intermittent Exotropia After Successful Corrective Surgery - Peng, Tingting; Xu, Meiping; Zheng, Fuhao; Zhang, Junxiao; Chen, Shuang; Lou, Jiangtao; Wang, Chunxiao; Wang, Yuwen; Yu, Xinping (Frontiers in Neuroscience, 2021)
PURPOSES: To study the longitudinal rehabilitation of binocular visual function in adolescent intermittent exotropia (IXT) after successful surgery and compare the results with those of a normal population. The role of binocular function in ocular alignment stability was also evaluated postoperatively. METHODS: In this prospective study, 30 adolescents with IXT successfully corrected after 1 month were followed for 12 months, and 30 normal children were enrolled as controls. Stereopsis, the fusional vergence amplitude, sensory fusion, and accommodative flexibility were measured to assess binocular function at baseline, and six and 12 months postoperatively. RESULTS: The deviation was -32.00±8.60 prism dioptres (PD) at distance and -36.0±9.10 PD at near preoperatively with an average exodrift of 4.20±4.47 PD and 4.97±5.64 PD at 12 months postoperatively (P=0.664). Distance stereoacuity and near stereoacuity improved from 1 to 12 months postoperatively (p=0.025, p=0.041, respectively). Compared with the controls, the fusional convergence reserve at distance (p=0.025) and near (p=0.033) and fusion reserve ratio at distance (p=0.000) and near (p=0.000) remained subnormal, while sensory fusion (p=0.237), distance stereopsis (p=0.120), and the fusional divergence amplitude at distance (p=0.168) were normal. However, there were no significant correlations between binocular functions at 1 month postoperatively and postoperative drift. CONCLUSIONS: Binocular function significantly improved from before to after successful corrective surgery and continued to improve from 1 to 12 months postoperatively in adolescents with IXT. No significant correlations were found between binocular functions at 1-month postoperatively and ocular alignment stability.